2013
DOI: 10.1089/bari.2013.0002
|View full text |Cite
|
Sign up to set email alerts
|

Mental Healthcare Utilization in Patients Seeking Bariatric Surgery: The Role of Attachment Behavior

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…All but one study used valid and reliable methods of data collection. This study was given a poorer rating for this criterion as the researchers generated their own questions regarding mental healthcare utilisation behaviour and this was not assessed for validity or reliability (Aarts et al, 2013). It should be noted that while rated favourably for their primary data collection methods, two studies (Harrington, 2008;Pratt et al, 2016) reported using selfreported weight measurements from the participants which are subject to bias and inaccuracy as participants are likely to misreport their weight.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…All but one study used valid and reliable methods of data collection. This study was given a poorer rating for this criterion as the researchers generated their own questions regarding mental healthcare utilisation behaviour and this was not assessed for validity or reliability (Aarts et al, 2013). It should be noted that while rated favourably for their primary data collection methods, two studies (Harrington, 2008;Pratt et al, 2016) reported using selfreported weight measurements from the participants which are subject to bias and inaccuracy as participants are likely to misreport their weight.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Furthermore, attachment anxiety has been found to be associated with mental healthcare utilization in patients seeking bariatric surgery. 16 In addition, in a study by Sockalingam et al, an association between attachment avoidance and poor mental health quality of life was observed. 17 It is as yet unknown whether attachment representations might impact the postoperative level and course of quality of life.…”
mentioning
confidence: 94%